Rate of Increase in Workload Determines the Mobilization Rate But Not the Degree of Increase in ECG Parameters (Baltic Journal of Sport and Health Sciences, 2015)
Background. The aim of this study was to compare the peculiarities of the dynamics of cardiovascular functional state indices during bicycle ergometry by applying the steep or slow increase in workload.Methods. Twenty five  males attending health promotion sport clubs took part in two cardiovascular testing procedures by performing graded exercise stress, i.e. increase in workload every 1 min, and increase in workload every 6 min, and they exercised till the inability to continue the task or unless distressing cardiovascular symptoms supervened; 12 lead ECG was recorded and analysed.Results. The steep increase of registered cardiovascular parameters was observed at onset of exercising and the rate of was in dependence on the rate of the increase in workload. Registered maximal changes of heart rate, JT interval, and the ratio JT/RR as functional state indices at the moment of refusing to continue the graded exercise test were at the same level while applying the steep or slow increase in workload.Conclusions. The rate of increase in workload determines the mobilization rate but not the degree of increase of ECG parameters. Maximal changes of heart rate, JT interval, and the ratio JT/RR as functional state indices at the moment of refusing to continue the graded exercise test were at the same level while applying the steep or slow increase in workload.Keywords:  cardiovascular system, graded exercise stress, functional state